Designing and manufacture solar turbines - Mohamad Yazid, Mohamad Yassin (2010)
This report shows the design and fabrication of a solar turbine. The objective of the report is to develop the procedures to design and fabricate a prototype solar turbine to generate energy. This report also describes the ideas and products of current solar turbines which are available around the world. Design generation is showed and solid three dimensional structures modelling of the solar turbine was developed with computer aided design software. Material selection and the reason behind the selection are shown based on criteria predetermined. Based on the selection, aluminium alloy and mild steel is selected. The result from the testing of the solar turbine shows that the solar turbine able to generate electricity. Ideas of improvement for the solar turbine also provided to further improve the solar turbine.